Sri Lanka's quest for a reformed constitution: Lessons froma lost opportunity - PULLE, Austin I. (Institutional Knowledge at Singapore Management University, 2019)
The history of Sri Lanka is highly instructive of the dynamics of constitutional evolution in a post-colonial, multi-ethnic, and economically challenged Asian nation. Sri Lanka is one of the few ex-colonies where constitutional change has happened without military involve ment. Citizens have changed their government10 times by generally fair and free elections. In the first three decades after independence, the country’s judiciary enjoyed an enviable reputation for independence, integrity, and competence.The public service, though poorly re warded and resourced, maintained a praiseworthy standard of administrative impartiality and competence. Sri Lanka had, and still has, one of the highest rates of literacy in the de veloping world and scores creditably on human development indicators. Despite these im pressive achievements, the country has a chequered record of constitutional government since independence. It has been ruled for long periods under emergency rule, and the nation’s two republican constitutions have a poor record of maintaining constitutional democracy and basic rights and freedoms.The nation’s most recent efforts at constitutional reform, des pite some notable successes, have stalled as a consequence of hyper-partisanship and oppor tunistic political strategizing. This article examines the post-independence constitutional history of the nation, prognosticates its prospects of constitutional revival, and draws im portant lessons from the failure of the current constitutional project.